PRELIMINARY REVISION OF SWIETENIOIDEAE (MELIACEAE) IN THAILAND - Ximu, Chen; Pongumphai, Somneuk (วารสารวนศาสตร์ไทย, 2022)
Four genera, 9 species of the Subfamily Swietenioideae in Thailand are treated in this revision They are 1. Toona : T. ciliata M. J. Roem., T. microcarpa (C.D.C.) Harms, T sureni (B1.) Merr.; 2. Swietenia : S. macrophylla King, S. mahogani (L. ) Jacq. 3. Chukrasia : C. tabularis A. Juss.; 4. Xylocarpus : X. granatum Koenig, X. moluccensis (Lam.) M. J. Roem., X. rumphii (Kostel.) Mabb. Identification keys to genera and species, as well as the distribution ranges and ecology of species are provided. A brief historical review of the family is given.